2013
DOI: 10.1136/heartjnl-2013-304717
|View full text |Cite
|
Sign up to set email alerts
|

Key recommendations and evidence from the NICE guideline for the acute management of ST-segment-elevation myocardial infarction

Abstract: The acute management of ST-segment-elevation myocardial infarction (STEMI) has seen significant changes in the past decade. Although the incidence has been declining in the UK, STEMI still gives rise to around 600 hospitalised episodes per million people each year, with many additional cases resulting in death before hospital admission. In-hospital mortality following acute coronary syndromes has fallen over the past 30 years from around 20% to nearer 5%, and this improved outcome has been attributed to variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…In spite of advances in diagnosis and treatment of critically ill patients throughout the recent decades, the triage, diagnostic and therapeutic management of these patients during the first week of ICU treatment still represents a major challenge. The promptness and accuracy of the initial decisions during the initial course of disease are of immense importance for the subsequent outcome of sepsis [ 47 ] or cardiogenic shock [ 48 ]. Inversely, failure of initiating the adequate therapy during the first phase of the disease may critically affect the mortality of these patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of advances in diagnosis and treatment of critically ill patients throughout the recent decades, the triage, diagnostic and therapeutic management of these patients during the first week of ICU treatment still represents a major challenge. The promptness and accuracy of the initial decisions during the initial course of disease are of immense importance for the subsequent outcome of sepsis [ 47 ] or cardiogenic shock [ 48 ]. Inversely, failure of initiating the adequate therapy during the first phase of the disease may critically affect the mortality of these patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…If there is an anticipated delay of >120 minutes from the time of first medical contact, fibrinolysis should be administered. Patients presenting to [12] Fibrinolysis and pharmaco-invasive strategies In most subSaharan countries, access to PPCIcapable facilities is limited. Fibrino lysis is therefore the first choice reperfusion therapy.…”
Section: Immediate Managementmentioning
confidence: 99%
“…Stable patients should receive antiplatelet therapy and anticoagulation with unfractionated heparins or LMWHs. [12] Failed fibrinolysis The 12lead ECG should be repeated 60 (tPA) 90 (streptokinase) minutes after fibrinolysis to assess therapeutic success. Failed fibrinolysis is indicated by failure of the ST elevation to reduce by >50% with or without persistent myocardial ischaemia.…”
Section: Immediate Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Time is of the essence: animal models have demonstrated that nearly 50% of salvageable myocardium is lost within the first hour of coronary artery occlusion, and two-thirds within 3 hours. 2 The recently published National Institute for Health and Care Excellence guideline recommends that patients with ST-segment elevation myocardial infarction in the presence of cardiogenic shock presenting within 12 hours of symptom onset should receive coronary angiography with primary percutaneous coronary intervention (PCI). 13 For patients presenting greater than 12 hours after the onset of the ST-segment elevation myocardial infarction, the likelihood of benefit may be limited and the consensus group recommends that decisions be made on a case-by-case basis.…”
Section: Treatment Strategiesmentioning
confidence: 99%